Digital Resources as a Way to Increase the Motivation of Economic Specialties Students in Studies of Mathematics - Irina Lebedeva; Larisa Norik; Stepan Lebedev (Educational Challenges, 2022)
The purpose of the work is to analyze the technical, methodical and psychological aspects of digitalization in education and, in particular, the methods of ensuring the effectiveness of independent work of students in the conditions of e-learning. The main attention is paid to the problem of the influence of interactive educational technologies on the formation of external and internal motivation of students of economic specialties to study mathematical disciplines.